2014
DOI: 10.1039/c3ra46396f
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin, a promising anti-cancer therapeutic: a review of its chemical properties, bioactivity and approaches to cancer cell delivery

Abstract: The development of new anti-cancer treatments with greater efficacy and fewer side effects remains a significant challenge of modern scientific and medical research. Curcumin, a natural polyphenol found in the dietary spice turmeric, has been demonstrated to inhibit cancer cell survival and proliferation, and to induce apoptosis without promoting the development of side effects. However, due to its sparing solubility and low bioavailability, curcumin has not yet been clinically used to treat cancer. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
153
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(153 citation statements)
references
References 115 publications
0
153
0
Order By: Relevance
“…During the past few decades, this agent has been extensively investigated for its pharmacological role that includes hepatoprotective and nephroprotective functions (Kiso et al, 1983;Venkatesan, 1998;Venkatesan et al, 2000). It has been shown that potent antiinflammatory as well as anti-cancer activities (Jurenka 2009;Salem et al, 2014). Several studies on the antimicrobial and .…”
Section: Introductionmentioning
confidence: 99%
“…During the past few decades, this agent has been extensively investigated for its pharmacological role that includes hepatoprotective and nephroprotective functions (Kiso et al, 1983;Venkatesan, 1998;Venkatesan et al, 2000). It has been shown that potent antiinflammatory as well as anti-cancer activities (Jurenka 2009;Salem et al, 2014). Several studies on the antimicrobial and .…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin has intensively been investigated, thanks to its impact on body health (Soni et al 2011): for its anti-oxidant properties; because it appears to slow the growth of tumour cells (Naksuriyaa et al 2014;Salem et al 2014) and even to be able to kill them; it can lower cholesterol levels and reduce obesity; able to stimulate muscle regeneration after trauma (Thaloor et al 1999) corrugate skin diseases; is a healing herb for the liver, spleen, stomach, intestines, lungs and blood; can prevent and cure Alzheimer's disease and can reduce inflammatory reactions (Ammon et al 1993). …”
Section: Advantages Of Curcuminmentioning
confidence: 99%
“…Various methodologies have been examined to deal with the solubility and bioavailability limits of curcumin and to enhance its solubility and to convey it to cancer cells (25). Early clinical studies imply that nanoparticles are advantageous for cancer therapy attributable to its capability of more focused localization in the tumor microenvironment (26).…”
Section: Introductionmentioning
confidence: 99%